2017
DOI: 10.3390/membranes7040067
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Comprehensive Tensile Relationship in Electrospun Silk Fibroin/Polycaprolactone Nanofiber Membranes

Abstract: The mechanical properties of electrospun nanofiber membranes are critical for their applications. A clear understanding of the mechanical properties that result from the characteristics of the individual fiber and membrane microstructure is vital in the design of fiber composites. In this reported study, silk fibroin (SF)/polycaprolactone (PCL) composite nanofiber membranes were preparedusing an electrostatic spinning technology. The nanofiber orientation distribution (FOD) of the membrane was analyzed using m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…Besides, it should be noted that the formation of intermolecular interaction between SFs and gelatin rendered the structural integrity of nanofiber mats and yielded the increase in mechanical properties (Zhu et al, 2015;Du et al, 2016;Selvaraj and Fathima, 2017). Moreover, according to morphological changes, higher gelatin content appeared to give rise to higher crosslinking density with resulting fiber fusion, thereby decreasing the porosity and increasing fiber entanglement leading to the strength enhancement (Simonet et al, 2014;Yin et al, 2017).…”
Section: Contact Angle and Water Uptake Capacitymentioning
confidence: 99%
“…Besides, it should be noted that the formation of intermolecular interaction between SFs and gelatin rendered the structural integrity of nanofiber mats and yielded the increase in mechanical properties (Zhu et al, 2015;Du et al, 2016;Selvaraj and Fathima, 2017). Moreover, according to morphological changes, higher gelatin content appeared to give rise to higher crosslinking density with resulting fiber fusion, thereby decreasing the porosity and increasing fiber entanglement leading to the strength enhancement (Simonet et al, 2014;Yin et al, 2017).…”
Section: Contact Angle and Water Uptake Capacitymentioning
confidence: 99%
“…The initial toe region is attributed to the stretching of coiled collagen fibers, which is followed by a second stage where further elongation of the straightened collagen fibers results in a steep rise in tensile stress until the tissue attains maximum extensibility . On the other hand, polymeric scaffolds showed a relatively linear mechanical behavior as shown by us (Figure F,G) and others . This could be attributed to the relatively straight electrospun fibers as observed by SEM (Figure C) and absence of undulation, which are found in the wavy collagen fibers of native heart valves.…”
Section: Resultsmentioning
confidence: 51%
“…31 On the other hand, polymeric scaffolds showed a relatively linear mechanical behavior as shown by us ( Figure 1F,G) and others. 31,[39][40][41][42] This could be attributed to the relatively straight electrospun fibers as observed by SEM ( Figure 1C) and absence of undulation, which are found in the wavy collagen fibers of native heart valves. Another reason of this nonlinear behavior of native valves could be the higher degree of heterogeneity of native valve ECM fibers than synthetic polymers, which have varying fiber lengths and crosslinking percentages.…”
Section: Fabrication Of Anisotropic Fibrous Scaffoldsmentioning
confidence: 71%
“…It has been shown that lateral contraction of nonwoven mats is ascribable to the buckling of fibers that are initially perpendicular or laterally oriented with respect to the loading direction, whereas fibers oriented along the loading axis undergo further alignment [ 38 ]. The mechanical properties of fibrous membranes thus depend on both the mechanical properties of the single fibers making up the membrane and the structure of the membrane itself, for example, how tight the fibers are packed and interconnected, and whether the fibers show any preferential orientation [ 38 40 ].…”
Section: Resultsmentioning
confidence: 99%